Production, Characterization, and Properties of Biochar - Zainab, Ngaini; Nur Aqilah, Makshut; Rafeah, Wahi; Showkat Ahmad, Bhawani (Springer Singapore, 2024)
Biochar-based research has been widely studied due to its superb physio-chemical properties and versatile applications. Numerous carbonization techniques of biomass have been introduced to form unique properties of biochars through thermochemical decomposition from the conventional to the latest technology (i.e., muffle, microwave, and tube pyrolysis) with higher porosity. During pyrolysis, the biowaste materials steadily transformed themselves into porous structured spherical shape particles with smaller particle sizes and higher surface area distributions. Nanostructure biochar showed a distinctive and ideal material for transdisciplinary usage due to its outstanding chemical, physical, and biological elements. Biochar has adaptable applications as fertilizer for soil amendment and also as an adsorbent for the removal of organic pollutants, dyes, and heavy metals. This chapter also describes the advancement in technology for the bioconversion of agricultural wastes into value-added products, which provides an eco-friendly alternative for a sustainable waste management system and benefits mankind.